Dietary fiber intake amount and knowledge level of adult women: A cross-sectional study - Gezer, Ceren; Demir, Zeynep (Refik Saydam National Public Health Agency (RSNPHA) turkhijyen@rshm.gov.tr, 2019)
Objective: The aim of this study is evaluating the relation between dietary fiber intake amount and dietary fiber knowledge level of adult women lived in Afyonkarahisar city center. Methods: The sample of the research was composed of 385 adult women live in Afyonkarahisar city center. Body weight, height, waist circumference, hip circumference measurements were measured. The 24-hour retrospective food consumption record technique was used to determine the amount of daily fiber intake, and Dietary Fiber Knowledge Scale was used to determine fiber knowledge level. Required statistical applications were carried out with Statistical Package for the Social Sciences 18.0 statistical program. Results: The mean value of daily dietary fiber intake and mean value of total dietary fiber knowledge score of the individuals were determined as 17.2 ± 4.17 g and 5.2 ± 1.65, respectively. No statistically significant difference were found between individuals' daily intake of dietary fiber and dietary fiber knowledge scale score according to age, education level and occupation. However, as the age group increased, dietary fiber knowledge scores increased (p > 0.05). In addition, it was determined that the self-employed occupations had the lowest daily fiber intake and total score of the dietary fiber knowledge scale, whereas those of the civil servants were the highest. No statistically significant difference was found between daily dietary fiber intake and dietary fiber knowledge scale score of individuals according to body mass index, waist circumference, waist/hip ratio and waist/height ratios. No correlation was determined between daily fiber intake and dietary fiber knowledge scale score (p > 0.05). Conclusion: In conclusion, dietary fiber knowledge level and the amount of fiber intake of adult women living in the Afyonkarahisar city center were low. In order to raise the knowledge level of women about fiber, it may be useful to create practical, interactive training programs in public education centers. Multicentre descriptive and experimental studies with wider sample size may be planned to investigate the factors that affect the fiber intake and fiber knowledge level of individuals in detail.; Amaç: Bu çalişmada Afyonkarahisar şehir merkezinde yaşayan kadin bireylerin diyet posasi alim miktarlari ile diyet posasi bilgi düzeyleri arasindaki ilişkinin değerlendirilmesi hedeflenmiştir. Yöntem: Araştirma örneklemini Afyonkarahisar şehir merkezinde yaşayan 385 yetişkin kadin oluşturmuştur. Vücut ağirliği, boy uzunluğu, bel çevresi, kalça çevresi ölçümleri yapilmiştir. Günlük diyet posasi alim miktarini saptamak için 24 saatlik geriye dönük besin tüketim kayit tekniği, diyet posasi bilgi düzeyinin belirlenmesi için Diyet Posasi Bilgi ölçeği kullanilmiştir. Gerekli istatistik uygulamalar Statistical Package for the Social Sciences 18.0 istatistik programi ile gerçekleştirilmiştir. Bulgular: Bireylerin günlük diyet posasi alim miktari ortalamasi 17.2±4.17 g, diyet posasi bilgi ölçeği toplam puan ortalamasi 5.2±1.65 olarak saptanmiştir. Bireylerin günlük diyet posasi alim miktari ve diyet posasi bilgi ölçeği puanlarinda yaş, eğitim durumu ve mesleğe göre istatistiksel olarak anlamli bir farklilik belirlenmemiştir. Ancak yaş grubu yükseldikçe diyet posasi bilgi ölçeği puanlari artiş göstermiştir (p > 0.05). Ayrica serbest meslekle uğraşanlarin diyet posasi alim miktari ve diyet posasi bilgi ölçeği toplam puani en düşük, memurlarin ise en yüksektir (p > 0.05). Bireylerin günlük diyet posasi alim miktari ve diyet posasi bilgi ölçeği puanlarinda beden kütle indeksi, bel çevresi, bel/kalça orani ve bel/boy orani siniflamalarina göre istatistiksel olarak bir farklilik belirlenmemiştir. Bireylerin günlük diyet posasi alim miktarlari ve diyet posasi bilgi düzeyi ölçeği puanlari arasinda ilişki bulunmamiştir (p > 0.05). Sonuç: Sonuç olarak Afyokarahisar merkezinde yaşayan yetişkin kadinlarin diyet posasi alim miktari önerilerin altinda ve diyet posasi bilgi düzeyi düşüktür. Kadinlarin diyet posasi ile ilgili bilgi düzeyinin yükseltilmesi için halk eğitim merkezlerinde uygulamali ve etkileşimli eğitim programlari oluşturulmasi yararli olabilir. Daha geniş örneklem büyüklüğüne sahip, çok merkezli, diyet posasi alimi ile diyet posasi bilgi düzeyini etkileyen faktörlerin daha detayli irdeleneceği tanimlayici ve deneysel çalişmalar planlanabilir. © 2019, Refik Saydam National Public Health Agency (RSNPHA).; © 2019, Refik Saydam National Public Health Agency (RSNPHA).
Yetişkin kadinlarin diyet posasi alim miktari ve bilgi düzeyi: Kesitsel bir çalişma
Keywords: Beslenme; Bilgi; Dietary fiber; Diyet posasi; Kadin sağliği; Knowledge; Nutrition; Women's health